2005
DOI: 10.1111/j.1365-2559.2005.02045.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐inducible factor‐1α is associated with angiogenesis, and expression of bFGF, PDGF‐BB, and EGFR in invasive breast cancer

Abstract: In invasive breast cancer, HIF-1alpha is associated with angiogenesis, and expression of growth factors bFGF and PDGF-BB, and the receptor EGFR. Thus, agents targeting HIF-1 may combine different pathways of inhibiting breast cancer growth, including angiogenesis and growth factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
118
1
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(129 citation statements)
references
References 48 publications
8
118
1
2
Order By: Relevance
“…In addition to its role in up-regulating glycolysis in response to hypoxia, HIF-1α is also the main transcription factor for vascular endothelial growth factor (VEGF), which stimulates angiogenesis [168,[180][181][182]. HIF-1α is part of the IGF-1/ PI3K/Akt signaling pathway that also indirectly influences expression of β FGF, another key angiogenesis growth factor [168,183]. Hence the sustained vascularity of tumors can be linked mechanistically to the metabolic requirements of substrate level phosphorylation necessary for tumor cell survival.…”
Section: Sustained Vascularity (Angiogenesis)mentioning
confidence: 99%
“…In addition to its role in up-regulating glycolysis in response to hypoxia, HIF-1α is also the main transcription factor for vascular endothelial growth factor (VEGF), which stimulates angiogenesis [168,[180][181][182]. HIF-1α is part of the IGF-1/ PI3K/Akt signaling pathway that also indirectly influences expression of β FGF, another key angiogenesis growth factor [168,183]. Hence the sustained vascularity of tumors can be linked mechanistically to the metabolic requirements of substrate level phosphorylation necessary for tumor cell survival.…”
Section: Sustained Vascularity (Angiogenesis)mentioning
confidence: 99%
“…HIF-1a induces transcription of genes that are involved in angiogenesis, cell survival, proliferation and promotes an aggressive tumor phenotype. 31,32 Several studies demonstrated high microvessel count and high microvessel density in tumors with fibrotic focus, especially in case a fibrotic focus is relatively large and harbors necrosis. 13,14 The fibroblasts occupying a fibrotic focus are reported to be highly proliferative and have the ability to express proteinase, which is crucial for developing metastases.…”
Section: Featurementioning
confidence: 99%
“…38,39 In tumors, various growth factors aberrantly secreted as part of paracrine or autocrine loops, have been implicated in stabilizing or up-regulating at transcriptional level the HIF1a. [40][41][42] To test whether in EOC cells HIF1a is inducible by PDGF, immortalized epithelial ovarian cancer cells were treated with PDGF BB in the presence or absence of imatinib, PD98059 and rapamycin. Cells were maintained in low oxygen atmosphere (2% O2) and HIF1a was measured in nuclear protein fractions by immunoblotting.…”
Section: Vegf Is Expressed In Ovarian Tumors and Is Secreted By Primamentioning
confidence: 99%